2017
DOI: 10.1002/app.45921
|View full text |Cite
|
Sign up to set email alerts
|

Toward poly(furfuryl alcohol) applications diversification: Novel self‐healing network and toughening epoxy–novolac resin

Abstract: Poly(furfuryl alcohol) bioresin (PFA) was synthesized and utilized through two distinct alloying strategies. It was crosslinked by a bismaleimide (BMI) via a Diels-Alder (DA) reaction. The novel PFA-BMI polyadduct network was spectrally, thermally, and thermo-mechanically characterized and its thermally repeatable self-healing behavior was visually established. The network showed a high pyrolytic thermostability (char yield 51% at 600 8C). PFA was also used for modification of epoxy-novolac resin (EP). EP hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…To the best of our knowledge, only one previous study has utilized DA reaction to prepare thermally reversible organic–inorganic IPN, and no semi‐IPN materials with thermoreversibility and self‐healing properties have been reported previously. In our earlier papers, we reported self‐healing DA networks by employing dimethylformamide (DMF) . It is a necessary solvent which has also been used in the majority of works in this field .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only one previous study has utilized DA reaction to prepare thermally reversible organic–inorganic IPN, and no semi‐IPN materials with thermoreversibility and self‐healing properties have been reported previously. In our earlier papers, we reported self‐healing DA networks by employing dimethylformamide (DMF) . It is a necessary solvent which has also been used in the majority of works in this field .…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier papers, we reported self‐healing DA networks by employing dimethylformamide (DMF) . It is a necessary solvent which has also been used in the majority of works in this field . This is a toxic solvent with high boiling point causing serious problems particularly when it must be removed during the curing process or before of the process.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The present research deals with incorporation of a furan-modified epoxy resin into the system to compensate the mechanical weakness and improve other characteristics. Therefore, DGEBA was firstly furfurylated to induce DA reactivity to the epoxy resin structure.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies on the PFA-BMI polyadduct network, with thermo-healing behavior, has been reported. [13] However, the sample were highly brittle presenting poor mechanical characteristics. Therefore, in the present work, to improve the bio-resin network properties, first, a furfurylated epoxy resin (FER) was synthesized and a PFA/FER hybrid DA network (HDAN) was obtained by BMI crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the self‐healing polymer composite has attracted increasing attention, as it is able to solve the aforesaid problem . There are basically two types of self‐healing polymers, i.e., extrinsic and intrinsic materials .…”
Section: Introductionmentioning
confidence: 99%